ANALISIS KINERJA KEUANGAN UKM BAKSO DI WILAYAH KOTA SEMARANG - Widiastuti Tri; Budiati Yuli; Niati Asih (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2018)
Behavioral finance approach is one of the important breakthroughs in the development of financial studies. Responsible financial behavior related to financial management and decision making processes and can allocate revenue appropriately and effectively. This study aims to analyze the financial performance of meatballs maker business in the city of Semarang. The research used qualitative method, data collecting technique through in-depth interview conducted on key informant. The informants included Chairman of Noodle and Meatball Society, Chairman of Manunggal Jaya Noodle and Meatball, Chairman of Noodles Society and Sido Rukun Bakso and Chairman of Noodles and Meatballs Traders Association (APMISO). Data analyze techniques using Miles and Hubermans model. Test the validity of data by credibility test through extension of observation and triangulation. Research results revealed that the owner of UMKM Bakso in Semarang City area is divided into three groups of UMKM Bakso where masin each group there are three clusters in managing their finances that is traditional, semi modern and modern. The result of triangulation shows that financial knowledge, financial management and financial behavior are interrelated to improve financial performance of UMKM Bakso owner, because financial knowledge, financial management and financial behavior can determine the direction of where the company will be run to achieve business goals, so it is necessary to make various efforts to improve the financial knowledge of UMKM Bakso owner. Therefore stakeholders should consider developing activities to improve financial knowledge for UMKM owners so that they are able to manage finances in an orderly and orderly manner and are able to perform well decisions. Activities to improve knowledge in managing finances can be training, seminars, and socialization.Keywords: Financial Behavioral, Financial Management, Financial Knowledge, Financial Performance